Caffeic acid phenethyl ester induced cell cycle arrest and growth inhibition in androgen-independent prostate cancer cells via regulation of Skp2, p53, p21(Cip1) and p27(Kip1) - Lin, Hui-Ping (Oncotarget, 2015)
Prostate cancer (PCa) patients receiving the androgen ablation therapy ultimately develop recurrent castration-resistant prostate cancer (CRPC) within 1–3 years. Treatment with caffeic acid phenethyl ester (CAPE) suppressed cell survival and proliferation via induction of G1 or G2/M cell cycle arrest in LNCaP 104-R1, DU-145, 22Rv1, and C4–2 CRPC cells. CAPE treatment also inhibited soft agar colony formation and retarded nude mice xenograft growth of LNCaP 104-R1 cells. We identified that CAPE treatment significantly reduced protein abundance of Skp2, Cdk2, Cdk4, Cdk7, Rb, phospho-Rb S807/811, cyclin A, cyclin D1, cyclin H, E2F1, c-Myc, SGK, phospho-p70S6kinase T421/S424, phospho-mTOR Ser2481, phospho-GSK3α Ser21, but induced p21(Cip1), p27(Kip1), ATF4, cyclin E, p53, TRIB3, phospho-p53 (Ser6, Ser33, Ser46, Ser392), phospho-p38 MAPK Thr180/Tyr182, Chk1, Chk2, phospho-ATM S1981, phospho-ATR S428, and phospho-p90RSK Ser380. CAPE treatment decreased Skp2 and Akt1 protein expression in LNCaP 104-R1 tumors as compared to control group. Overexpression of Skp2, or siRNA knockdown of p21(Cip1), p27(Kip1), or p53 blocked suppressive effect of CAPE treatment. Co-treatment of CAPE with PI3K inhibitor LY294002 or Bcl-2 inhibitor ABT737 showed synergistic suppressive effects. Our finding suggested that CAPE treatment induced cell cycle arrest and growth inhibition in CRPC cells via regulation of Skp2, p53, p21(Cip1), and p27(Kip1).